Key Performance Indicators in Claims Management: Definition of a Set of Indicators for the Evaluation of the Medico-Legal Activity - Scopetti, Matteo; Padovano, Martina; Manetti, Federico; Gatto, Vittorio; D’Errico, Stefano; Santurro, Alessandro; Frati, Paola; Fineschi, Vittorio (Current Pharmaceutical Biotechnology, 2021)
Background: In recent decades, in the field of healthcare, awareness of the problems inherent to the quality has steadily increased. Currently, the evaluation of healthcare activities is one of the ways in which health systems regulate internal relationships and define strategic decisions. Objective: The study aims to describe in detail the entire process of developing a group of Key Performance Indicators for monitoring and implementing the management of litigation due to medical liability. Particularly, the objective is to centralize and standardize the indicators to provide scientifically reliable data on claims management to hospital professionals responsible for strategic choices. Methods: The study was conducted to analyze data relating to the claims management at Umberto I General Hospital in Rome from 2012 to 2018. All claims reported were classified according to a selection of the categories coded in the International Classification for Patient Safety system, the economic features, and the chronological references of the main management extrajudicial and judicial phases. The Process Analysis Method was followed to develop significant indicators for measuring the performance and the quality of claims management. Results and Conclusion: The results obtained demonstrate how the assessment of performance in claims management can potentially lead to greater risk control with significant repercussions in terms of reduction of disputes, speed in settling claims, reduction of management times, planning of loss prevention measures, and implementation of quality of care.
Keywords: patient safety